A Comparison of the Effectiveness of Mindfulness-Based Cognitive Therapy and Cognitive-Behavioral Play Therapy in Improving the Time Perception of Children with Attention Deficit Hyperactivity Disorder (ADHD) - Kazemi, Nasim; Kooshki , Shirin; Emamipour , Susan (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study aimed to determine the effectiveness of mindfulness-based cognitive therapy and cognitive-behavioral play therapy in improving the time perception of children with attention deficit hyperactivity disorder (ADHD). Methods: The present study was quasi-experimental with a pretest-posttest design, and a control group with a two-month follow-up. The statistical population consisted of all people who visited Shayan Rehabilitation Clinic in 2019-2020. A total of 59 individuals were selected by a convenience sampling method and were randomly assigned to experimental and control groups. Participants were evaluated with the Conners rating scale- short-revised form (1960), and the theoretical time reproduction test by Mirlou and Asadzadeh (2011). The experimental group received Jackson Mindfulness-based Cognitive Therapy (2018), and another experimental group received Cognitive-Behavioral Play Therapy by Jafari et al. (2002) in twelve sessions twice a week. Data were analyzed using the repeated-measures analysis of variance. Results: The results indicated that the mean scores of short time perception (F=4.01, P=0.001) were significantly different between the two experimental groups, and the difference in the mindfulness-based cognitive therapy group in the post-test was significantly higher than the pre-test and the cognitive-behavioral play therapy, and there was also a significant difference between mean scores of long time perception (F=13.45, P=0.001) in the two experimental groups. The difference in the mindfulness-based cognitive therapy group in the post-test was greater than the pre-test and the cognitive-behavioral play therapy, and there was a better improvement in the participants, and the difference was also statistically significant (P=0.01). Conclusion: Given the significant effect of mindfulness-based cognitive therapy, and cognitive-behavioral play therapy on time perception of children with attention deficit hyperactivity disorder, it is suggested using these two methods to increase the children's health.